Managed or Supervised: Exploring Citizenship of the Child - Artazo, Gabriela; Barrionuevo, Marcelo (Universidad Nacional de Villa María, 2015)
This essay recovers inputs collected from different research projects developed on the theme of children and rights in the City of Villa María, Córdoba, by different teams that make the Bachelor of Social Work at the National University of Villa María. It is also the experience in specific programs and interventions in state devices that put focus on children in general and child poverty in particular feeds. The paper seeks to problematize through an analysis of the ways and mechanisms to implement childhood institutions, the tension between consolidation and validity of equalities framework and formal protection through sanctions childhood laws now in force and those real forms that institutional devices to take a reading of the situation of children and subsequent intervention. From this perspective, there are elements that position away from children in a stage of active citizenship, subsumed in complex mechanisms of domination and protection, such forms of patronage that old paradigm that regulated the lives of poor children in our country and believed surpassed today.